Modeling Human Neurological and Neurodegenerative Diseases: From Induced Pluripotent Stem Cells to Neuronal Differentiation and Its Applications in Neurotrauma - Bahmad, Hisham; Hadadeh, Ola; Chamaa, Farah; Cheaito, Katia; Darwish, Batoul; Makkawi, Ahmad-Kareem; Abou-Kheir, Wassim (Frontiers in Molecular Neuroscience, 2017)
With the help of several inducing factors, somatic cells can be reprogrammed to become induced pluripotent stem cell (iPSCs) lines. The success is in obtaining iPSCs almost identical to embryonic stem cells (ESCs), therefore various approaches have been tested and ultimately several ones have succeeded. The importance of these cells is in how they serve as models to unveil the molecular pathways and mechanisms underlying several human diseases, and also in its potential roles in the development of regenerative medicine. They further aid in the development of regenerative medicine, autologous cell therapy and drug or toxicity screening. Here, we provide a comprehensive overview of the recent development in the field of iPSCs research, specifically for modeling human neurological and neurodegenerative diseases, and its applications in neurotrauma. These are mainly characterized by progressive functional or structural neuronal loss rendering them extremely challenging to manage. Many of these diseases, including Parkinson’s disease (PD), Huntington’s disease (HD), Amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (AD) have been explored in vitro. The main purpose is to generate patient-specific iPS cell lines from the somatic cells that carry mutations or genetic instabilities for the aim of studying their differentiation potential and behavior. This new technology will pave the way for future development in the field of stem cell research anticipating its use in clinical settings and in regenerative medicine in order to treat various human diseases, including neurological and neurodegenerative diseases.